Parenting roles and peer interactions support children’s social development at TK ABA 02 Bumiaji - Khaatijah, Yayak; Tinus, Agus; Wurianto, Arif Budi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The study is important for understanding how parenting styles and peer interactions influence children's social development during the critical early childhood period. The objective of this study was to examine the application of parenting styles and children's social interactions as efforts to encourage social development in TK ABA 02 Bumiaji Kindergarten. A qualitative approach was employed, utilizing a case study design to collect data. This data was collected through direct observation, interviews with teachers and parents, and documentation. The data were analyzed using descriptive analysis. The findings indicated that the parenting styles employed by teachers and parents exerted a positive influence on children's social development, particularly in their capacity to interact, share, and cooperate with peers. Furthermore, social interactions among children both within and outside the classroom context have been shown to foster peer relationships. In conclusion, positive parenting and supportive social interactions at TK ABA 02 Bumiaji enhance children's social development, highlighting the importance of parents and educators in maintaining consistent support during early childhood to optimize social competencies.